Vowel migration in sung Filipino text and perceived intelligibility - Dimaculangan, Jaharra Mae V.; Felias, Rachelle Anne S. (2008.)
In this project, an intelligibility measurement tool for sung migrated vowels was realized in a Graphical User Interface (GUI) platform. The measurement tool will help aid voice students in recognizing whether the migrating techniques in classical singing compromise the intelligibility of the sung text. The system uses sung vowels recorded by Classical singers from the University of the Philippines (UP) College of Music. Intelligibility tests were conducted to obtain the ground truth for vowel classification based on perception. Parameters, such as formats, special envelopes, Mel Frequency Cepstral Coefficients (MFCCs) and vowel triangles, were studied to determine their relation to vowel intelligibility. Verified parameters which can discriminate all five distinct Filipino vowels are the nine MFCCs and the formant values. The verified parameters comprise the database of the vowel classifier. MFCC extraction was done using PLP algorithm and formant detection was done using Linear Predictive Coding (LPC). Necessary training of the system was done to produce the acoustic model. Classification based on formant values and MFCCs resulted in over-all accuracy of 46.4% and 68.1% for the training set.
Undergraduate Student Project (B.S., EEE)--University of the Philippines, Diliman.
Keywords: Speech processing -- Digital techniques; Signal processing; Vowel migration